The causal effect of religious and environmental identity on green preferences: A combined priming and stated choice experiment - Daniel Engler; Elke D. Groh; Andreas Ziegler (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
Using a stated choice experiment, we find that a prime that makes environmental identity salient makes people behave greener, whereas it does not if it makes religious identity salient. Further-more, we discover non-linear priming effects for environmental identity, which means that rais-ing the salience of highly environmentally oriented respondents or respondents without envi-ronmental identity does not change behavior while it does for respondents with a medium level strength of identity. Methodologically, our study combines for the first time a priming experi-ment with a stated choice (SC) experiment and uses a respondent specific status quo alternative in the empirical analysis with mixed logit models.
Keywords: Q42; Q54; A13; C25; Z12; 330; Climate change; religious and environmental identity; green electricity; renewable energy; priming; stated choice experiment; mixed logit models